Consumer Behavior - Yohana Ditya Puspita; Mustika Putri Fatimah Ardiyanti; Mariam Nasser Alrashed (Journal of International Conference Proceedings (JICP), 2018)
Aerofood ACS (Aerowisata Catering Service) is a service provider company that has been around for 40 years in Garuda Indonesia flight. ACS Aerofood Company as a service provider, trying to provide the best service to consumers. In a modern era, a lot of people requires practical and high quality comfort. From this cause the number of consumer desires are various kinds. This study will analyze the influence of customer behavior in the running of a company. Consumer behavior could lead us to predict the changing and understanding of people (customers) needs and wants nowadays. This paper analyzes the issues of consumer behavior that exist in the company and aims to advocate alternative solutions related to its division as part of the supply chain. Based on data collected and analyzed for the company, this paper should use descriptive analysis, and qualitative analysis. Keywords : customer, macro and micro aspect, market research, provider